Radiographic evaluation of furcal perforations sealed with different materials in dogs' teeth - José Roberto Vanni; Álvaro Della-Bona; José Antônio Poli De Figueiredo; Giovani Pedro; Douglas Voss; Patrícia Maria Poli Kopper (University of São Paulo, 2011)
OBJECTIVE: The objective of this work was to evaluate, using radiographic images, the behavior of four materials used to repair root perforations in dogs' teeth. Material and METHODS: Second and third premolars of 6 dogs were used. The 48 teeth were randomly divided into 4 groups (n=12) and the perforations were sealed with one of the following materials: MTA, AH Plus, Vitremer and gutta-percha. Dogs were submitted to general anesthesia, teeth were radiographed and pulp was accessed. Perforations were done, at the maximum curve of the pulp floor, sealed and the accessed coronal cavity was filled with glass ionomer cement (Vidrion R). After 90 days, the dogs were sacrificed and the last x-ray image was taken. Images were analyzed for the presence/absence of periodontal lesions at the perforation region. Data were analyzed statistically by chi-square test at 5% significance level. RESULTS: There were no statistically significant differences (p>0.05) among AH Plus, Vitremer and gutta-percha groups. MTA produced the smallest number of periodontal lesions (p<0.05). CONCLUSIONS: It may be concluded that none of the tested materials was able to preserve the integrity of the periodontal tissues in the furcation region, and the use of MTA resulted in the least formation of adjacent periodontal bone lesions revealed by the radiographic comparisons.